Lessons learned while implementing an HIV/AIDS care and treatment program in rural Mozambique - Moon, Troy D. (2010)
Mozambique has severe resource constraints, yet with international partnerships, the nation has placed over 145,000 HIV-infected persons on antiretroviral therapies (ART) through May-2009. HIV clinical services are provided at > 215 clinical venues in all 11 of Mozambique’s provinces. Friends in Global Health (FGH), affiliated with Vanderbilt University in the United States (US), is a locally licensed non-governmental organization (NGO) working exclusively in small city and rural venues in Zambézia Province whose population reaches approximately 4 million persons. Our approach to clinical capacity building is based on: 1) technical assistance to national health system facilities to implement ART clinical services at the district level, 2) human capacity development, and 3) health system strengthening. Challenges in this setting are daunting, including: 1) human resource constraints, 2) infrastructure limitations, 3) centralized care for large populations spread out over large distances, 4) continued high social stigma related to HIV, 5) limited livelihood options in rural areas and 6) limited educational opportunities in rural areas. Sustainability in rural Mozambique will depend on transitioning services from emergency foreign partners to local authorities and continued funding. It will also require “wrap-around” programs that help build economic capacity with agricultural, educational, and commercial initiatives. Sustainability is undermined by serious health manpower and infrastructure limitations. Recent U.S. government pronouncements suggest that the U.S. President’s Emergency Plan for AIDS Relief will support concurrent community and business development. FGH, with its Mozambican government counterparts, see the evolution of an emergency response to a sustainable chronic disease management program as an essential and logical step. We have presented six key challenges that are essential to address in rural Mozambique.